2017
DOI: 10.18202/jamal.2017.12.7068
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Kinerja Usaha Mikro, Kecil, Dan Menengah

Abstract: litian ini bertujuan untuk mengeksplorasi peran faktor internal dan eksternal terhadap kinerja 164 Usaha Mikro, Kecil, dan Menengah (UMKM) di daerah Depok dan Jakarta. Metode yang digunakan adalah uji korelasi dan diperdalam dengan uji regresi. Penelitian ini menunjukkan bahwa kinerja UMKM dipengaruhi oleh faktor internal yaitu manajemen operasional, pemasaran, dan teknis. Selain itu, situasi industri juga turut memengaruhi kinerja UMKM. Apabila faktor-faktor tersebut diperkuat, hal ini akan meningkatkan posis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Indonesia masih sangat bergantung pada pertumbuhan sektor Usaha Mikro Kecil Menengah (UMKM) dan sektor ini menjadi faktor kunci dalam perkembangan ekonomi nasional (Hanggraeni, Sulung, Nikmah, & Hapsari, 2017). UMKM di Indonesia merupakan salah satu soko guru perekonomian Indonesia selain koperasi.…”
Section: Pendahuluanunclassified
“…Indonesia masih sangat bergantung pada pertumbuhan sektor Usaha Mikro Kecil Menengah (UMKM) dan sektor ini menjadi faktor kunci dalam perkembangan ekonomi nasional (Hanggraeni, Sulung, Nikmah, & Hapsari, 2017). UMKM di Indonesia merupakan salah satu soko guru perekonomian Indonesia selain koperasi.…”
Section: Pendahuluanunclassified
“…Internal factors in Bangli MSMEs include marketing, access to capital, entrepreneurial skills, human resources, financial knowledge, and business plans; (2). Hanggaeni et al (2017) obtained the results of research that MSMEs' performance is influenced by internal factors namely operational management, marketing, and technical. In addition, the industrial situation also influences the performance of MSMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on the influence of external and internal factors on the performance of MSMEs which shows the results that external factors have a positive and significant effect on the performance of MSMEs (Hanggraeni et al, 2017(Hanggraeni et al, , 2019Munizu, 2010). Research conducted by (Lanang et al, 2014) found that external and internal factors significantly influence the performance of MSMEs, but the most dominant influence is internal factors.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of MSMEs to the Indonesian economy includes the ability to absorb 97% of the total workforce and can collect up to 60.4% of the total investment (Kementerian Koordinator Bidang Perekonomian Republik Indonesia, 2021). Seeing the contribution of the MSME sector gives an illustration that Indonesia is still dependent on the growth of the MSME sector, and makes the MSME sector a key factor in national economic development (Hanggraeni et al, 2017;Sadalia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%